A Simple Combination Approach for Costal Cartilage Augmentation Rhinoplasty. Issue 2 (March 2020) - Qiao, Congzhen; Yu, Wenxin; Gao, Wei; Qiu, Yajing; Lin, Xiaoxi
Abstract : Abstract: Autologous costal cartilage graft is optimal for augmentation rhinoplasty but with complications including markedly visible graft margins and dorsal contour irregularities. Therefore, the authors introduced the diced costal cartilage graft to smoothen the margins of bilateral spreader graft for nasal dorsum augmentation. A total of 6 patients were recruited for this augmentation rhinoplasty. The pre- and postoperative photographs were taken for improvement evaluation. During a mean follow-up of 15 months, none of the patients developed major complications that may require removal or revision of the costal cartilage grafts. Five patients (80%) were very satisfied with the aesthetic outcome. This simple algorithm facilitates the substantial augmentation and removes the visibility of dorsal graft in the costal cartilage rhinoplasty for the East Asian population.